Healthcare Costs and Resource Use of Patients with Dupuytren Contracture Treated with Collagenase Clostridium Histolyticum or Fasciectomy: A Propensity Matching Analysis - Zah V; Pelivanovic J; Tatovic S; Vukicevic D; Imro M; Ruby J; Hurley D (Dove Medical Press, 2020)
Vladimir Zah,1 Jovana Pelivanovic,1 Simona Tatovic,1 Djurdja Vukicevic,1 Martina Imro,1 Jane Ruby,2 David Hurley2 1Health Economics and Outcomes Research Department, ZRx Outcomes Research Inc., Mississauga, ON, Canada; 2Medical Affairs, Endo Pharmaceuticals Inc., Malvern, PA, USACorrespondence: Vladimir ZahZRx Outcomes Research Inc, Mississauga, ON, CanadaTel +1 416-953-4427Email vzah@outcomesresearch.caObjective: Studies examining differences in US healthcare resource utilization (HCRU) and associated healthcare costs between collagenase clostridium histolyticum (CCH) and fasciectomy for Dupuytren contracture (DC) are limited. This study evaluated US HCRU and direct healthcare cost for the treatment of DC in privately insured patients using insurance claims.Methods: This retrospective observational cohort study analyzed data from large nationwide insurance claims databases; it included individuals diagnosed with DC between July 1, 2011, and June 30, 2017, who were adults at index date (date of first treatment: CCH or fasciectomy). Participants had continuous health plan coverage 24 months pre-index and 12 months post-index date. All-cause and DC-related HCRU and healthcare costs from the payers’ perspective were compared between propensity score–matched cohorts. Generalized linear models assessed factors associated with all-cause total healthcare costs.Results: Of 83,983 patients diagnosed with DC, 1932 adults receiving fasciectomy and 953 adults receiving CCH were included. The mean ± standard deviation total all-cause healthcare cost was significantly lower with CCH than with fasciectomy (US$11,897 ± US$14,633 versus US$15,528 ± US$22,254, respectively; P< 0.001). After propensity score matching, 702 and 999 patients remained in the CCH and fasciectomy cohorts, respectively. In this analysis, all-cause and DC-related total costs were significantly lower in the CCH cohort versus the fasciectomy cohort (all-cause: US$11,044 ± US$12,856 versus US$12,912 ± US$19,237, respectively, P=0.02; DC-specific: US$3417 ± US$3671 versus US$5800 ± US$4985, P< 0.001), mainly due to the lower frequency of outpatient visits. CCH treatment and the use of a consumer-driven healthcare plan were associated with lower healthcare costs.Conclusion: Based on matched cohort data, adjusted 1-year healthcare costs for CCH-treated individuals were significantly lower compared with costs for fasciectomy-treated individuals.Keywords: injection, surgery, insurance claims, retrospective database study